Environmental Risk Assessment of Fuel Oil Spill Incidents in Indonesian Archipelagic Waters: Vulnerability Mapping and Mitigation Strategies - Winarno; Marihot Simanjuntak; Markus Yando Manurung; Yok Suprobo (International Journal of Marine Engineering Innovation and Research, 2026)
Indonesia's position as the world's largest archipelagic state — operating domestic shipping networks through the globally significant Coral Triangle and other ecologically sensitive marine environments — creates one of the world's most consequential maritime pollution risk landscapes. This study conducts a comprehensive environmental risk assessment of fuel oil spill incidents in Indonesian archipelagic waters, integrating accident probability modelling, ecosystem vulnerability mapping, and response capacity analysis into a spatially explicit Integrated Spill Risk Index. A mixed-methods methodology was applied, combining negative binomial regression analysis of 1,847 domestic shipping incident records (2015–2024) with AIS traffic exposure data across six geographic zones, composite marine environmental sensitivity mapping from Allen Coral Atlas, Global Mangrove Watch, and BPS Indonesia livelihood data, NOAA GNOME drift trajectory modelling, and stakeholder interviews with 28 maritime safety and environmental stakeholders. Results identify the Makassar Strait (risk index 0.89) and Banda Sea (0.84) as Critical priority zones requiring immediate investment. Despite having lower incident probability, the Banda Sea registers the highest environmental vulnerability score (0.96) due to its Coral Triangle location, extensive seagrass and mangrove coverage, and coastal communities with over 80% fish dependency. Three immediate priority recommendations emerge: establishment of dedicated OSRO pre-positioning at Makassar Port and Ambon; mandatory AIS-based vessel traffic management with speed restrictions through ecologically sensitive Makassar Strait segments; and strengthened SMS verification and P&I insurance requirements for domestic tankers and bulk carriers operating Critical-zone corridors. The study provides the first integrated spill risk index for Indonesian domestic shipping routes, offering a prioritization framework for the Ministry of Transportation, KPLP, and environmental authorities.